Chemically modified graphene/PEDOT:PSS nanocomposite films for hydrogen gas sensing - Zheng, Yang; Lee, Duckhee; Koo, Hye Young; Maeng, Sunglyul (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
In this study, we report the preparation of chemically modified graphene/(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) nanocomposites and their application in hydrogen (H-2) gas sensing materials. The aqueous dispersions of graphene oxide (GO) and reduced graphene oxide (rGO) nanosheets were synthesized and further doped into the solution of PEDOT:PSS in dimethylsulfoxide (DMSO). Both the GO/PEDOT:PSS and rGO/PEDOT:PSS composite devices showed a decrease in the resistance upon hydrogen exposure at room temperature. The GO/PEDOT:PSS, a strong p-type material, formed by rectifying contact with tungsten was evaluated for the H-2 gas sensing and identified as a contact-controlled type. The rGO/PEDOT:PSS, a weak n-type material, forming an ohmic contact with tungsten was investigated for its H-2 gas sensing and identified as a body-controlled type. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: REDUCED GRAPHENE OXIDE; TEMPERATURE; GRAPHITE; POLYMER; SENSOR